PENGARUH KOMPOSISI ASAM SULFAT (H₂SO₄) SEBAGAI STIMULANSIA PADA BERBAGAI DIAMETER DALAM MENINGKATKAN PRODUKTIVITAS GETAH PINUS - Nur Hidayanti; Witno Witno; Hadija Azis Karim (Universitas Andi Djemma Palopo, 2021)
Tapping pine sap at PT Inhutani I using the quarre method and giving stimulants in the form of sulfuric acid concentration (H₂SO₄) was carried out to increase the productivity of pine resin. The purpose of this study was to determine the composition of sulfuric acid (H₂SO₄) as a stimulant at various diameters on the productivity of pine resin, with a ratio of 10%, 20%, and 30% sulfuric acid composition used. The study results obtained latex productivity data for 30 days, with the highest average being at a concentration of 20% (K2) with a diameter of 60 cm (D1) with a value of 33.66 g. In contrast, the lowest productivity was found at a concentration of 0% (K0) with a diameter of 60 cm (D1) of 4.66 g. Analysis of variance showed that the concentration treatment had a significant effect on the productivity of pine resin, with an F-count value of 4.02 an F-table value of 3.01 at the 5% level. The results of the Tukey test showed that the stimulant concentration of K2 (20%) had a significantly different productivity effect from stimulants and the concentrations of K1 (10%) and K3 (30%).